Pedagogical strategies for teaching legal translation: bridging language and law - Yatsyshyn, Nataliia (Волинський національний університет імені Лесі Українки, 2024)
It takes a profound integration of language and legal education to teach legal translation. Legal translation requires proficiency in specific legal terminology and requires more than just language skills. Because law is an international field, especially in organizations such as the EU, translators need to be technologically savvy and have the ability to translate across cultural boundaries accurately. To close the language-legal gap in legal translation training, this research analyzes important educational approaches.
Keywords: legal translation; English; Law; translation; 34(082)( 477)